Word into image. writers on screenwriting - Mazursky, Paul (The Foundation, 1984)
An interview with screenwriter Paul Mazursky. He talks about his early work and his progression from serious writer to performer to television comedy writer to screenwriter-director. Clips from Mazursky's films show how he speaks to the changes people face, yet are entertaining.